(untitled) (Cadernos de Sociomuseologia, 2025)
The creation of the international committees SOMUS (Social Museology) and SUSTAIN (Museums and Sustainable Development), within the framework of ICOM, represents a milestone in the consolidation of sustainability agendas in the museum field. SOMUS stems from a trajectory led by the Ibero-American context, as heir to the Mesa of Santiago (1972) and the International Movement for a New Museology (MINOM), legitimizing community-based and insurgent practices that claim the centrality of social justice and community participation in museums. SUSTAIN, in turn, formalizes a path that began in the 1960s and 1970s and was deepened in 2018, strongly connected to Nordic and European sustainable development agendas. This process articulates historical demands that are today associated with the 2030 Agenda and the Paris Agreements, with increasing outreach in Africa and Asia. Far from being configured as competing instances, both committees find points of convergence by positioning museums as agents of social transformation and by reinforcing the cross-cutting nature of the SDGs. The analysis proposed here demonstrates that the articulation between social and sustainability dimensions opens new horizons for contemporary museology, affirming museums as spaces of citizenship, diversity, and the construction of fairer and more sustainable futures. Keywords: Social Museology; Sustainable Development; ICOM; Community Participation; SDGs